Surface morphology of molybdenum silicide films upon low-energy ion beam sputtering. (6th June 2018) - Gago, R; Jaafar, M; Palomares, F J
Abstract: The surface morphology of molybdenum silicide (Mo x Si1− x ) films has been studied after low-energy Ar + ion beam sputtering (IBS) to explore eventual pattern formation on compound targets and, simultaneously, gather information about the mechanisms behind silicide-assisted nanopatterning of silicon surfaces by IBS. For this purpose, Mo x Si1− x films with compositions below, equal and above the MoSi2 stoichiometry ( x = 0.33) have been produced by magnetron sputtering, as assessed by Rutherford backscattering spectrometry (RBS). The surface morphology of silicon and silicide films before and after IBS has been imaged by atomic force microscopy (AFM), comprising conditions where typical nanodot or ripple patterns emerge on the former. In the case of irradiated Mo x Si1− x surfaces, AFM shows a marked surface smoothing at normal incidence with and without additional Mo incorporation (the former results in nanodot patterns on Si). The morphological analysis also provides no evidence of ion-induced phase separation in irradiated Mo x Si1− x . Contrary to silicon, Mo x Si1− x surfaces also do not display ripple formation for (impurity free) oblique irradiations, except at grazing incidence conditions where parallel ripples emerge in a more evident fashion than in the Si counterpart. By means of RBS, irradiated Mo x Si1− x films with 1 keV Ar + at normal incidence have also been used to measure experimentally the (absolute) sputtering yield and rate of Si and Mo x Si1− x materials. The analysis reveals that, under the present working conditions, the erosion rate of silicides is larger than for silicon, supporting simulations from the TRIDYN code. This finding questions the shielding effect from silicide regions as roughening mechanism in metal-assisted nanopatterning of silicon. On the contrary, the results highlight the relevance of in situ silicide formation. Ripple formation on Mo x Si1− x under grazing incidence is also attributed to the dominance of sputtering effects under this geometry. In conclusion, our work provides some insights into the complex morphological evolution of compound surfaces and solid experimental evidences regarding the mechanisms behind silicide-assisted nanopatterning.